Through the wardrobe : how C.S. Lewis created Narnia - Maslo, Lina (Balzer + Bray, an imprint of HarperCollins Publishers, 2020)
A lyrical nonfiction picture book about the inspired life of C.S. Lewis, the beloved author of the Chronicles of Narnia--from Free as a Bird author-illustrator Lina Maslo. Perfect for fans of The Important Thing About Margaret Wise Brown and Some Writer!: The Story of E.B. White. This nonfiction picture book is an excellent choice to share during homeschooling, in particular for children ages 4 to 6. It's a fun way to learn to read and as a supplement for activity books for children. As a child, Clive Staples Lewis imagined many things ... heroic animals and knights in armor and a faraway land called Boxen. He even thought of a new name for himself--at four years old, he decided he was more of a Jack. As he grew up, though, Jack found that the real world was not as just as the one in his imagination. No magic could heal the sick or stop a war, and a bully's words could pierce as sharply as a sword. So Jack withdrew into books and eventually became a well-known author for adults. But he never forgot the epic tales of his boyhood, and one day a young girl's question about an old family wardrobe inspired him to write a children's story about a world hidden beyond its fur coats ... a world of fauns and queens and a lion named Aslan. A world of battles between good and evil, where people learned courage and love and forgiveness. A magical realm called Narnia. And the books he would write about this kingdom would change his life and that of children the world over.